A collocation method based on reproducing kernel for a modified anomalous subdiffusion equation. Issue 1 (28th October 2013) - Jiang, Wei; Chen, Zhong
Abstract In this article, we proposed a collocation method based on reproducing kernels to solve a modified anomalous subdiffusion equation problem. We give constructively the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3z3s9b61" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ε</alternatives>‐approximate of the equation whose coefficients are determined optimally by solving a system of linear equations. The final numerical experiments demonstrate that the proposed method is simple, effective, and easy to implement. Copyright © 2012 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 30: 289–300, 2014